المخاطر القانونية لعقد المناولة الصناعية: إكراهات قانون المنافسة: The legal risks of the industrial subcontracting: Competition law constraints - صاري نوال (Journal of North African Economies, 2025)
From a legal point of view, the study outlines some of the legal risks (competition law) that need to be taken into account in the Industrial subcontracting in its aspects related to intellectual property rights. European Union law has been used to illustrate how it has dealt with the issue, as well as Algerian law, which has focused on industrial subcontracting as a tool for the development of small and medium-sized enterprises (SMEs). On the basis of the adopted hypothesis, the study concludes by clarifying when competition law is violated in an industrial subcontracting and how competition policy accompanies partnership agreements between sub-contractor SMEs.